1959
DOI: 10.1099/00221287-20-3-473
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Heterotrophic Micro-Organisms from Soil for Ability to Form Nitrite and Nitrate

Abstract: SUMMARY: A total of 978 cultures of heterotrophic organisms were isolated from twelve actively nitrifying soils ; each isolate was tested for ability to form nitrite or nitrate in glucose peptone broth. None of the isolates yielded substantial amounts of nitrite ; concentrations found did not exceed 2 pg. nitrite-N/ml. Almost 7 yo of the isolates formed nitrite-N in excess of 0.2 pg./ml., while slightly over 2 yo yielded more than 0.5pg./ml. Fungus isolates were the most numerous and most active nitrite produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2
1

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(42 citation statements)
references
References 13 publications
0
39
2
1
Order By: Relevance
“…First, the relatively low substrate supply used in these experiments (1 g·L -1 ) must not be toxic for MS30 nitrification activity. Secondly, it has been reported that complex organic matter favored nitrite production by heterotrophic bacteria (Eylar and Schmidt 1959). However, it has also been shown that several organic nitrogen compounds can inhibit heterotrophic nitrification (Doxtader and Alexander 1965).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the relatively low substrate supply used in these experiments (1 g·L -1 ) must not be toxic for MS30 nitrification activity. Secondly, it has been reported that complex organic matter favored nitrite production by heterotrophic bacteria (Eylar and Schmidt 1959). However, it has also been shown that several organic nitrogen compounds can inhibit heterotrophic nitrification (Doxtader and Alexander 1965).…”
Section: Discussionmentioning
confidence: 99%
“…First, numerous organic and inorganic substances can be used as N-sources for heterotrophic nitrification (Focht and Verstraete 1977), and an organic carbon source is necessary not only for growth of the organisms, but also for nitrification of at least inorganic N-sources (Hylin and Matsumoto 1960;Verstraete and Alexander 1972b). Concerning the products of heterotrophic nitrification, hydroxylamine is often the intermediate product, and hydroxamates can be the main product (Verstraete 1974); but the final product of heterotrophic nitrification generally is nitrite (Obaton et al 1968;Verstraete andAlexander 1972a, 1972b;Castignetti and Hollocher 1984), although sometimes some nitrate formation was observed in bacterial cultures (Gunner 1963;Verstraete and Alexander 1972a;Castignetti and Gunner 1981;Papen et al 1989), and most fungi mainly excrete nitrate (Eylar and Schmidt 1959;Marshall and Alexander 1962). In addition, contrary to autotrophic nitrifiers, some heterotrophic microorganisms can carry out dual activity.…”
Section: Introductionmentioning
confidence: 96%
“…Heterotrophic nitrification is predominantly carried out by fungi (Landi et al 1993) which gain energy from compounds that belong to more recalcitrant organic N pools in soil (Paul 2007). Therefore, NO 3 -production via organic N oxidation is often carried out by acid tolerant fungi in forest soils (Eylar and Schmidt 1959;Stroo et al 1986). …”
Section: Production and Consumption Of No 3 -mentioning
confidence: 98%
“…The first large-scale screening of soil fungi for the ability to nitrify in pure culture was by Eylar and Schmidt (1959) who screened 751 soil fungi. Of these, only three produced significant levels of nitrate from amino-nitrogen.…”
Section: The Nitrifying Organisms Of Coniferous Forest Soils the Fungmentioning
confidence: 99%